ANALISIS KEMAMPUAN KEUANGAN DAERAH KABUPATEN MANGGARAI PROVINSI NTT TAHUN 1995-2010 - , Maria Ignasia Dedy Djeha ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is aimed to (1) measure and analyze fiscal capacity of Manggarai Regency based on Fiscal Autonomy Degree indicator (DOF), Routine Capacity Index (IKR), and PAD Performance Index (IPPAD)